Potential of functional candies from ethanol extracts of Myristica fragrans and Phyllanthus acidus as antioxidant and anti-anxiety agents: A comprehensive review - Fauzana, Anindita Azkia; Maheswari, Efada Aini Ayu; Angeline, Jennifer; Santoso, Azizah Bonitha Zahrah; I’tishom, Reny (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Anxiety disorders are a major global health burden, with recent WHO data indicating a 1.79% increase in case incidence rate (CIR) and a 6.25% rise in disability-adjusted life years (DALY) over the past five years. Conventional pharmacotherapies such as SSRIs and benzodiazepines are limited by adverse effects and dependency risks, highlighting the urgent need for safer, effective alternatives. Myristica fragrans (nutmeg) and Phyllanthus acidus (otaheite gooseberry) are rich in myristicin and flavonoids, respectively, both of which exhibit promising anxiolytic and neuroprotective properties. However, the synergistic efficacy and safety of their combined use remain underexplored. Methods: A comprehensive review was conducted following PRISMA guidelines. Out of 512 studies identified from Scopus, PubMed, ScienceDirect, and EBSCO, 36 met inclusion criteria after quality appraisal using CASP, with 2 clinical trials extracted for quantitative synthesis. Data extraction focused on changes in anxiety scores (e.g., HAM-A), stress biomarkers (cortisol, MDA), antioxidant enzyme activities (SOD, CAT), and neurochemical modulation (serotonin, GABA, dopamine). Findings: analysis revealed that combined administration of nutmeg and otaheite gooseberry extracts reduced anxiety scores by a weighted mean difference (WMD) of –7.3 (95% CI: –9.1 to –5.5, p<0.001) on the HAM-A scale compared to placebo. Cortisol levels decreased by 18.4% (p=0.002), while MDA levels dropped by 22.7% (p=0.001), and SOD activity increased by 31.6% (p<0.001) in preclinical models. Myristicin (500 mg/kg) produced significant anxiolytic effects via serotonergic and GABAergic modulation, while flavonoids (1.2–3.5% content) provided robust neuroprotection against oxidative stress. No antagonistic interactions or increased toxicity were observed; the combination outperformed single extracts and showed comparable efficacy to SSRIs and benzodiazepines with fewer adverse effects. Conclusions: The integration of Myristica fragrans and Phyllanthus acidus extracts offers a synergistic, natural therapeutic approach for anxiety disorders, combining potent anxiolytic and neuroprotective effects with an excellent safety profile. Novelty/Originality of this article: This review is the first to quantitatively demonstrate the synergistic anxiolytic and antioxidant efficacy of nutmeg and otaheite gooseberry extracts, supporting their development as innovative functional candies for mental health management.